(Un)steady as a Rock: Believing, in Times of Make-believe. (2nd January 2019) - Hällgren, Anna-Maria
Abstract : In order to broaden the possibilities for further, in-depth analysis of contemporary art in the light of climate change, the essay identifies and explores a recurrent phenomenon within contemporary art today: The frequent use of rocks and stones. Stones have, of course, played a quite significant role in the history of art, not least through skillfully crafted marble and grand earthworks. Within contemporary art today, however, everyday pebbles, cobbles and boulders have become a means to address the ecological crisis. By drawing upon the ongoing debate about the reorganization of knowledge, fostered by the awareness of climate change and discussed by Matthew Omelsky and Ian Baucom amongst others, this essay examines when and how stones became such a means. By reflecting upon artworks by Jimmie Durham, Adriane Wachholz, Silvia Noronha and Julian Charrière, it is suggested that stones are often used as a medium to transgress habitual and anthropocentric notions of time and temporality. Further, through their work, these artists have the potential to make us believe, in times of make-believe: Not only in the urgency of climate change, but also in a future to come.